Analysis of Blockchain Technology and Security Principles in Cryptocurrency Transactions according to the perspective of Islamic Economics: Case study : Smart Contract on the Ethereum Blockchain Network - Sihabudin, Fahmi; Achmad, Listian Indriyani; 'Ainulyaqin, Muhammad Hamdan; Midisen, Kisanda; Edy, Sarwo (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2022)
This study aims to understand the concept of security and privacy in blockchain technology through Islamic economics. Cryptocurrencies have been around for less than a decade, but they have caused divisions among religious scholars. Some Islamic scholars say that cryptocurrencies are haram or forbidden because they are based on speculation. Other scholars claim that cryptocurrencies are halal or permitted because they can be used for transactions that Islam considers legal. The debate over the legality of cryptocurrencies is complicated by the lack of a clear consensus among Islamic scholars. There is also disagreement over whether or not to allow investments in cryptocurrencies. This study uses a qualitative approach. Data collection was carried out using structured interviews with a number of respondents, including Islamic scholars and lecturers. The results of the study show that blockchain as a digital security transaction solution with its data decentralization is in line with the principles of Islamic Economics in the non-monetary field, but contradicts the principles of Islamic Economics in the monetary sector because of the obligation to follow the official Government in Monetary Policy.